Revenue-Maximising Elasticities of Taxable Income in Multi-Rate Income Tax Structures - John Creedy; Norman Gemmell (New Zealand Government, The Treasury, 2013)
The empirical literature on the elasticity of taxable income (ETI) sometimes questions whether estimated values are consistent with being on the revenue-increasing section of the Laffer curve, usually in the context of a single rate tax system or for top marginal rates. This paper develops conceptual expressions for this `Laffer-maximum' or revenuemaximising ETI for the multi-rate income tax systems commonly used in practice. Using the New Zealand income tax system in 2010 to illustrate its properties, the paper demonstrates that a wide range of revenue-maximising ETI values can be expected across individual taxpayers, across tax brackets and in aggregate.
Keywords: H24; H31; H26; 330; Income Tax Revenue; Elasticity of taxable income; revenue elasticity; Laffer Curve